EUS-guided fiducial placement for GI malignancies: a systematic review and meta-analysis - Coronel, Emmanuel; Cazacu, Irina M.; Sakuraba, Atsushi; Luzuriaga Chavez, Adriana Alexandra; Uberoi, Angad; Geng, Yimin; Tomizawa, Yutaka; Saftoiu, Adrian; Shin, Eun Ji; Taniguchi, Cullen M.; Koong, Albert C; Herman, Joseph M.; et al. (Gastrointestinal endoscopy, 2019)
Image-guided radiotherapy (IGRT) allows the delivery of radiation with high precision to a target lesion while minimizing toxicity to surrounding tissues. EUS provides excellent visualization of GI tumors and consequently is being used for fiducial placement with increased frequency. Our goal was to perform a systematic review and meta-analysis of studies evaluating the technical aspects, safety, and efficacy of EUS fiducial placement for IGRT in GI malignancies. A systematic literature search was carried out in the following databases: Medline, PubMed, Embase, Web of Science, and Cochrane Library, using Medical Subject Headings terms combined with text words. A random effects model was used to determine pooled proportions of technical success, migration, and adverse event rates. Heterogeneity was assessed using the I2 statistic. Publication bias was assessed visually using a funnel plot and by the Begg and Egger tests. Nine full articles and 5 abstracts reporting on 1155 patients, 49% from a single study by Dhadham et al, were included in the meta-analysis. The pooled rate of technical success was 98% (95% confidence interval [CI], 96-99). Moderate heterogeneity (I2 = 34.18) was present, which appeared to be due to variable sample sizes. Publication bias was present, suggesting that studies with less-substantial outcomes may have not been reported (Begg test, P = .87; Egger test, P < .01). Pooled rates for fiducial migration and adverse events were 3% (95% CI, 1.0-8.0) and 4% (95% CI, 3-7), respectively. Our meta-analysis showed that EUS-guided insertion of gold fiducials for IGRT is technically feasible and safe. Further controlled studies assessing its long-term effectiveness in GI malignancies are needed. [Display omitted]